Heteroduplex Analysis of the Sequence Relationships Between the Genomes of Kirsten and Harvey Sarcoma Viruses, Their Respective Parental Murine Leukemia Viruses, and the Rat Endogenous 30S RNA - Chien, Yueh-Hsiu (1979)
The sequence relations between Kirsten murine sarcoma virus (Ki-SV), Harvey murine sarcoma virus (Ha-SV), and a rat endogenous 30S RNA were studied by electron microscope heteroduplex analysis. The sequence relationships between the sarcoma viruses and their respective parental murine leukemia viruses (Kirsten and Moloney murine leukemia viruses), as well as between the two murine leukemia viruses, were also studied. The only observed nonhomology feature of the Kirsten murine leukemia virus/Moloney murine leukemia virus heteroduplexes was a substitution loop with two arms of equal length extending from 1.80 ± 0.18 kilobases (kb) to 2.65 ± 0.27 kb from the 3′ end of the RNA. It is believed that this feature lies in the env gene region of the viral genomes. The Ha-SV and Moloney murine leukemia virus genomes (respective lengths, 6.0 and 9.0 kb) were homologous in a 1.0 ± 0.05-kb region at the 3′ end and possibly over a 200-nucleotide region at the 5′ ends; otherwise, they were nonhomologous. Ha-SV and Ki-SV (length, 7.5 kb) were homologous in the first 4.36 ± 0.37-kb region from the 3′ end and in a 0.70 ± 0.15-kb region at the 5′ end. In between, there was a nonhomology region, possibly containing a short (0.23-kb) region of partial or total homology. The heteroduplex analysis between rat endogenous 30S RNA and Ki-SV shows that there are mixed regions of sequence homology and nonhomology at both the 5′ and 3′ ends. However, there is a large (4-kb) region of homology between Ki-SV and the rat 30S RNA in the center of the genomes, with only a small nonhomology hairpin feature. These studies help to define the regions of homology between the Ha-SV and Ki-SV genomes with each other and with the rat endogenous 30S RNA. These regions may be related to the sarcoma genicity of the viruses. In particular, the 0.7-kb region of homology of Ha-SV with Ki-SV at the 5′ ends may be related to the formation of a 21,000-dalton phosphoprotein in cells transformed by either virus.